2017
DOI: 10.1364/boe.8.003597
|View full text |Cite
|
Sign up to set email alerts
|

qF-SSOP: real-time optical property corrected fluorescence imaging

Abstract: Fluorescence imaging is well suited to provide image guidance during resections in oncologic and vascular surgery. However, the distorting effects of tissue optical properties on the emitted fluorescence are poorly compensated for on even the most advanced fluorescence image guidance systems, leading to subjective and inaccurate estimates of tissue fluorophore concentrations. Here we present a novel fluorescence imaging technique that performs real-time (i.e., video rate) optical property corrected fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…While the current processing time to invert diffuse reflectance maps to optical properties is typically on the order of 1 second, we recently demonstrated that this inversion time could be reduced significantly to approximately 10 ms [31]. Altogether this work lays the foundation of real-time quantitative optical imaging through an endoscope and its clinical translation, potentially enabling endoscopic implementation of current quantitative, widefield techniques [32][33][34].…”
Section: Discussionmentioning
confidence: 85%
“…While the current processing time to invert diffuse reflectance maps to optical properties is typically on the order of 1 second, we recently demonstrated that this inversion time could be reduced significantly to approximately 10 ms [31]. Altogether this work lays the foundation of real-time quantitative optical imaging through an endoscope and its clinical translation, potentially enabling endoscopic implementation of current quantitative, widefield techniques [32][33][34].…”
Section: Discussionmentioning
confidence: 85%
“…Quantitative fluorescence means absolute numbers can be attributed to signal for diagnostic purposes. Valdes et al 75 recently applied the principles of real-time optical properties imaging (SSOP) to the quantitative measurement of fluorescence (termed qF-SSOP), allowing to predict fluorescence concentration within 5% in various turbid media optical properties, and in real time, making it amenable to be used during surgery [ Fig. 8(a)].…”
Section: Sfdi and Fluorescencementioning
confidence: 99%
“…23,25,73,108 Recent work by Valdes et al has prototyped a real-time fluorescence measurement embodiment to facilitate translation to operating room and real-time scenarios. 75 SFDIderived subdiffusive endogenous reflectance and scattering contrast has also become a useful tool for classifying excised tissue types. The main goal for this is work is to enable intraoperative assessment of lumpectomy margins by differentiating between normal, fibroadenoma, ductal carcinoma in situ (DCIS), and invasive cancer.…”
Section: Oncology/cancermentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 For instance, fluorescence imaging to help surgeons visualizing structures of interest, such as lymph nodes, ureters, or micrometastasis, stands as an example where providing tissue-related information in real time plays a key role in clinical adoption. [15][16][17][18] Among all existing solutions, spatial frequency domain imaging (SFDI) has been recently developed with the unique capacity to provide rapidly quantitative diffuse information (absorption and reduced scattering) over large fields of view (typically, >10 × 10 cm 2 ). 14,19 Even more recently, the SFDI method has been improved to image optical properties more rapidly using two images 20 or even a single image.…”
Section: Introductionmentioning
confidence: 99%